Antihypertensive activity and molecular interactions of irbesartan in complex with 2‐hydroxypropyl‐β‐cyclodextrin. (21st July 2020) - Leonis, Georgios; Christodoulou, Eirini; Ntountaniotis, Dimitrios; Chatziathanasiadou, Maria V.; Mavromoustakos, Thomas; Naziris, Nikolaos; Chountoulesi, Maria; Demetzos, Costas; Valsami, Georgia; Damalas, Dimitrios E.; Tzakos, Andreas G.; Thomaidis, Nikolaos S.; et al.
Abstract: Irbesartan (IRB) exerts beneficial effects either alone or in combination with other drugs on numerous diseases, such as cancer, diabetes, and hypertension. However, due to its high lipophilicity, IRB does not possess the optimum pharmacological efficiency. To circumvent this problem, a drug delivery system with 2‐hydroxypropyl‐β‐cyclodextrin (2‐HP‐β‐CD) was explored. The 1:1 complex between IRB and 2‐HP‐β‐CD was identified through ESI QTF HRMS. Dissolution studies showed a higher dissolution rate of the lyophilized IRB–2‐HP‐β‐CD complex than the tablet containing IRB at pH = 1.2. DSC results revealed the differences of the thermal properties between the complex and various mixtures consisting of the two components, namely IRB and 2‐HP‐β‐CD. Interestingly, depending on the way the mixture preparation was conducted, different association between the two components was observed. Molecular dynamics (MD) simulations predicted the favorable formation of the above complex and identified the dominant interactions between IRB and 2‐HP‐β‐CD. In vitro pharmacological results verified that the inclusion complex not only preserves the binding affinity of IRB for AT1R receptor, but also it slightly increases it. As the complex formulation lacks the problems of the tablet, our approach is a promising new way to improve the efficiency of IRB. Abstract : An inclusion complex of antihypertensive drug irbesartan with 2‐hydroxylpropyl‐β‐cyclodextrin was prepared and characterized with a variety of biophysical and computational approaches. It was shown that the complex formulation as a drug delivery device significantly improved irbesartan's pharmacologic efficiency by enhancing its aqueous solubility.